A Capacity Associated with the Weighted Lebesgue Space and Its Applications - Guoliang Li; Guanglan Wang; Lei Zhang (Journal of Function Spaces)
In this paper, we focus on a further study of the weighted Lebesgue capacity associated with the following fractional heat equation: ∂t+−Δxαut,x=0, ∀α,t,x∈0,1×0,∞×ℝn,u0,x=fx, ∀x∈ℝn.. More properties of that capacity are explored, and applications to a trace inequality for the weak solution of the equation are considered.